Menyelaraskan Tradisi Dengan Teknologi: Transformasi Pendidikan Agama Katolik di Era Digital - Kurnia Saputra, Yohanes Chandra (Vocat : Jurnal Pendidikan Katolik, 2024)
The integration of technology in Catholic religious education creates new opportunities as well as challenges that need to be overcome. This research aims to develop a Catholic religious education model that integrates digital technology effectively without sacrificing the traditional values taught. Through a literature study approach, this research analyzed various digital tools and platforms that could be used in Catholic religious education, while identifying challenges and opportunities in adopting this technology. The research results showed that technology had potential to enrich students' learning experiences and support spiritual development, while enabling more interactive and flexible learning. However, it was important to ensure that technology integration did not reduce the focus on the moral and spiritual formation of students. This transformation also reflected the church's adaptation to the digital era, ensuring the relevance of religious teachings in modern times, and has the potential to increase the involvement of the younger generation in church life. Thus, this change was predicted to have a positive impact on students' learning experiences and their involvement in church life.